1995
DOI: 10.1063/1.113728
|View full text |Cite
|
Sign up to set email alerts
|

Giant magnetoresistance at 300 K in single crystals of La0.65(PbCa)0.35MnO3

Abstract: Giant magnetoresistance (GMR) at 300 K and 5.5 T with ΔR/R(0)=74% was observed in single crystals of La0.65(PbCa)0.35MnO3. The maximum GMR occurs exactly at the ferromagnetic–paramagnetic phase transition temperature (Tc). For T<Tc, the R(T) curve is closely related to the M(T) curve. A sign change in the curvatures of R(H) curves below and above Tc has been observed, indicating that two different mechanisms are responsible for the magnetic scatterings of the carriers in two separate temperature regions. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
30
0

Year Published

1997
1997
2010
2010

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(35 citation statements)
references
References 0 publications
5
30
0
Order By: Relevance
“…6 shows the temperature dependence of the resistance of the LCMO thin film with and without a magnetic field, as well as the MR of the thin film from 200 to 300 K. As compared with epitaxially grown thin films by the PLD method, the LCMO thin films we report here have a large value of MR. It is found that the MR of the LCMO film is 40% in a magnetic field of 5.5 T at 200 K. As the temperature elevated, the MR of the film increases and reaches the maximum of 85.4% at 259 K, which is similar to the MR of a single crystal of La 0.55 (CaPb) 0.35 MnO 3 reported by Liu et al [15]. Even at room temperature, the LCMO films prepared by the PFS method still retain a high value of MR (40%).…”
Section: The Epitaxial Growth Of the Thin Film Confirmed By Xrdsupporting
confidence: 81%
“…6 shows the temperature dependence of the resistance of the LCMO thin film with and without a magnetic field, as well as the MR of the thin film from 200 to 300 K. As compared with epitaxially grown thin films by the PLD method, the LCMO thin films we report here have a large value of MR. It is found that the MR of the LCMO film is 40% in a magnetic field of 5.5 T at 200 K. As the temperature elevated, the MR of the film increases and reaches the maximum of 85.4% at 259 K, which is similar to the MR of a single crystal of La 0.55 (CaPb) 0.35 MnO 3 reported by Liu et al [15]. Even at room temperature, the LCMO films prepared by the PFS method still retain a high value of MR (40%).…”
Section: The Epitaxial Growth Of the Thin Film Confirmed By Xrdsupporting
confidence: 81%
“…All of the samples show at least one well-defined peak in resistance as a function of temperature. Below the peak the resistivity drops sharply as has been observed previously for single crystal and thin film samples [15]. As the magnetic field is increased the value of peak resistance decreases monotonically.…”
Section: Magnetoresistance Measurementssupporting
confidence: 60%
“…For single crystals, the magnetoresistivity effect is found only in the vicinity of the transition temperature and at low temperatures it is not significant. For example, in single crystal La (Pb,Ca) MnO a magnetoresitivity effect of only 0.2% is observed at 5 K in a field of 5 T [15]. However, in many polycrystalline materials a substantial effect has been reported even at low temperatures [4,[16][17][18].…”
Section: Magnetoresistance Measurementsmentioning
confidence: 98%
“…Perovskite-type transition-metal oxides ABO 3 and their oxygen-deficient relatives exhibit a variety of interesting physical properties including high-temperature superconductivity, metal-insulator transition, and a variety of cooperative magnetic phenomena. Among them manganites have recently attracted particular attention because of the discovery of colossal negative magnetoresistance ͑CMR͒ in La 1Ϫx Sr x MnO 3 , 1 La 1Ϫx Ba x MnO 3 , 1 and related phases.…”
Section: Introductionmentioning
confidence: 99%